Personalized hydration requirements of runners - Cheuvront, S. N.; Kenefick, R. W. (International Journal of Sport Nutrition and Exercise Metabolism, 2022)
This study sought to (a) estimate how the duration of running influences sweat losses and contributes to the daily fluid requirement, and (b) empirically estimate the drinking rates required to prevent significant dehydration (=2% body weight as body water). Individual sweating data and running duration were obtained from male (n = 83) and female (n = 36) runners (n = 146 total observations) performing under highly heterogeneous conditions and over a range of exercise durations (33-280 min). Running <60 min/day increased daily fluid needs by a factor of 1.3, whereas running >60 min/day increased the daily fluid need by a factor of 1.9-2.3. Running <60 min/day generally required no fluid intake to prevent significant dehydration before run completion (31/35 runners). In contrast, running >60 min/day required more than 50% replacement of sweating rates to prevent the same (65/111 runners). Overall sweat losses ranged from ~0.2 to ~5.0 L/day, whereas the drinking rates required to prevent significant dehydration ranged from 0 to 1.4 L/hr. The characterization of sweat losses, sweat rate, and required drinking among runners in this study indicate wide individual variability that warrants personalized hydration practices, particularly when running is prolonged (>60 min) and performance is important. This study may serve as a useful guidepost for sports dietitians when planning and communicating fluid needs to athletes, as well as complement guidance related to both personalized programmed and thirst-driven drinking strategies.